A retrospective cohort study : the directly observed treatment short-course strategy (dots) and tuberculosis treatment outcomes at Vryheid during 2007 : facilty versus community based dots - Kikamba, C. N. (Stellenbosch : University of Stellenbosch, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.